2015
DOI: 10.3923/ijpbg.2015.228.237
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Inter-Relationship of Sesame Genotypes and their Traits Using Cluster Analysis and Principal Component Analysis Methods

Abstract: The study was carried out from 2011-2013 cropping seasons in three locations of Northern Ethiopia (a total of 7 environments) and thirteen sesame genotypes were evaluated. The objective of this study was to determine the interrelationship of the genotypes and their genetic divergence. The experiment was laid out in randomized complete block design with three replications. The thirteen sesame genotypes were grouped into four clusters based on the similarity of their agronomic traits and the dendrogram showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…In contrast to this, PCA1 was negatively associated with days to 50% flowering and 50% maturity (Figure 3). [11,14] also found similar results to this finding from their study on sesame genotypes.…”
Section: Ordination Of the Sesame Genotypes And Eir Agronomicsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast to this, PCA1 was negatively associated with days to 50% flowering and 50% maturity (Figure 3). [11,14] also found similar results to this finding from their study on sesame genotypes.…”
Section: Ordination Of the Sesame Genotypes And Eir Agronomicsupporting
confidence: 86%
“…[1] also found a significant difference of different agronomic traits of wheat evaluated across years. ere is a possibility for occurrence of such variation of genotypes in their agronomic traits across years and even across locations, and this may be both a challenge and an opportunity for plant breeding and breeders [11]. e highest grain yield of the sesame genotypes was recorded in the second growing season (2014).…”
Section: Performance Of the Sesame Genotypes Across The Reementioning
confidence: 99%
“…This indicates sesame grain yield and yield related traits were highly affected by the growing environments. And this is true for sesame both in rain fed ( Baraki et al., 2015a ; Tantawy et al., 2007 ; Nath et al., 2001 ) and irrigation production ( El Mahdi et al., 2007 ; Nadeem et al., 2015 ; Ebrahimian et al., 2019 ). ( El Mahdi et al., 2007 ) also reported that a sowing date difference in sesame significantly affects sesame seed yield and yield related traits under irrigation condition and this may be mainly sesame is highly sensitive to temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Principal component analysis (PCA) can effectively downsize the structure of a two-way Multi Environment Trial (MET) data matrix of genotypes (G) across different environments (E) dimension in a fewer dimensions and this method is considered to be efficient ( Cruz-Castillo et al., 1994 ). ( Crossa, 1990 ) stated that cluster analysis is a numerical arrangement technique that explains groups of individuals and hierarchical classification, which important to categorizes individuals into groups having the objective of studying associations in the data ( Zhang et al., 2008 ; Baraki et al., 2015a , 2015b ; Jinxiong et al., 1995 ). used cluster analysis and PCA in sesame to group sesame genotypes based on their agronomic traits and the authors suggested to scholars to manipulate PCA to efficiently downsize multiple traits from multiple environments in a fewer and understandable dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The highest intra-cluster distance observed in cluster I which indicates that the germplasm of cluster I was more diverged than any other cluster. There was comparative divergence of one cluster from another and higher divergence seen between clusters III and IV (2717.76) followed by clusters I and IV(1760.59), selection of lines to use them as parents for hybridization programme from these clusters will result in unique genotypes and generation of promising crossed material as proposed by [1,4,[11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%